Implementing Agile Methodologies in QA for Media and Telecommunications - Viharika Bhimanapati; Om Goel; Pandi Kirupa Gopalakrishna Pandian (Innovative Research Thoughts, 2022)
Implementing Agile methodologies in Quality Assurance (QA) within the media and telecommunications sectors represents a transformative shift in the approach to software development and testing. Traditional QA processes, often characterized by sequential and rigid stages, struggle to keep pace with the rapidly evolving demands of media and telecommunications applications. Agile methodologies offer a flexible and iterative approach that aligns more closely with the dynamic nature of these industries, promising enhanced responsiveness to changes, improved product quality, and greater customer satisfaction. This research explores the application of Agile methodologies in QA for media and telecommunications, focusing on the benefits, challenges, and best practices associated with this approach. The study begins with a comprehensive review of Agile principles and practices, including Scrum, Kanban, and Extreme Programming (XP), and examines their integration into QA processes. By transitioning to Agile, organizations can achieve continuous testing, early defect detection, and more frequent releases, which are crucial for keeping up with market demands and technological advancements.